EDUKASI PENYAKIT HIPERTENSI DAN KOMPLIKASINYA PADA POSYANDU LANSIA DI WILAYAH KERJA PUSKESMAS MENGWI I, KABUPATEN BADUNG - Agung Bagus Sista Satyarsa (Buletin Udayana Mengabdi, 2020)
Hypertension is a global problem because its prevalence continues to increase with age and lifestyle changes such as smoking, obesity, physical inactivity, and psychosocial stress. Based on the 2013 Riskesdas record, that the prevalence of hypertension in the elderly increases with increasing age groups; that is, at the age of 55-64 years is 45.9%, while in the age group 65-74 years and above 74 years the prevalence is 57.6% and 63.8% respectively. Management of hypertension such as diet compliance, adherence to taking hypertension medication, and environmental modification are important things that can control hypertension which can further prevent complications. In implementing this management of hypertension, it is important to support and motivate the elderly by various parties ranging from families, health workers to the community. One of the efforts to increase the understanding of the elderly about hypertension and its complications can be done through healthy exercise activities at the holding of the Elderly Integrated Healthcare Center. In addition, education carried out by young doctors to the elderly informally is expected to increase the understanding and awareness of the elderly to follow the recommended hypertension management so that it is expected that the elderly's blood pressure can remain controlled and avoid complications.